Influence of endometrial thickness and embryo placement distance from fundus in in-vitro fertilization treatment - Selvamani, Divya; Gurumoortthy, Madhuvanthi; Anandaraj, Abinaya; Elanchezhian, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: In-vitro fertilization–embryo transfer (IVF-ET) has become progressively popular as a treatment for different type of infertility issues. Implantation of the embryo is an essential step and depends on various factors that play pivotal role in influencing the pregnancy outcomes in IVF cycle. It directly impacts on the efficiency of embryo transfer procedure, site of embryo deposition, catheter loading technique, embryo placement distance from the fundus and thickness of endometrium. Methods: In the present retrospective study, data from IVF-ET treatment cycles conducted at Srushti Fertility Centre and Women’s Hospital, Chennai, for a period between October 2021 and February 2022 were analysed. Women were divided into four groups according to embryo placement distance from fundus post embryo transfer group 1: <10 mm, group 2: >10 to <15 mm, group 3: >15 to <20 mm and group 4: >20 mm. According to endometrial thickness they were divided into two groups, group A: 6-10 mm and group B: 10-14 mm. Clinical pregnancy were assessed between the groups. Results: Clinical pregnancy rates were higher in groups 2 and 3 when compared to embryo placement distance from fundus 62.3% and 82.2%, distance of 10 mm and 20 mm and endometrial thickness of more than 10 mm (group B) had higher clinical pregnancy rates 66.3% than (group A) 43.5%. Conclusion: Ideal ET depth and optimum endometrial thickness were found to influence the clinical pregnancy rates. Embryo placement at 10-20 mm from fundus and endometrial thickness of more than 10 mm is recommended for optimal clinical pregnancy outcomes.